HOW CROSS-BORDER SECURITIES HOLDINGS INFLUENCE MARKET INFORMATION TRANSMISSION DURING THE U.S. RECIPROCAL TARIFF SHOCK - Robinson Robinson; Buddi Wibowo (Prosiding Seminar Nasional dan Call Paper STIE Widya Wiwaha, 2025)
This study examines the short-term reactions of six international stock markets to the announcement of the United States’ tariff policy using an event study methodology. Grounded in the Efficient Market Hypothesis, market responses are expected to reflect rapid price adjustments to new information, while the financial linkage perspective suggests that countries with stronger investment exposure to U.S. investors may react more intensely. To test these theoretical expectations, the analysis focuses on abnormal returns (AR) surrounding the event window of −3 to +3 days, with countries classified into high and low groups based on the level of U.S. Resident Securities Holding. The empirical results reveal significant abnormal returns across several high-holding countries, particularly Japan, which shows strong anticipatory reactions prior to the announcement and notable corrections afterward. Canada and South Korea also demonstrate early and coordinated responses. Conversely, low-holding countries exhibit weaker and less systematic reactions; South Africa shows delayed negative movements, while Thailand and Turkey display minimal sensitivity to the policy shock. These findings support both hypotheses: markets exhibit significant abnormal returns during the event window, and financial exposure to U.S. investors amplifies the speed and magnitude of market reactions. Overall, the study provides evidence that cross-border portfolio linkages play a meaningful role in transmitting the impact of U.S. trade policy to global financial markets. The results highlight the importance of financial integration as a channel of international shock propagation and offer insights for policymakers and investors managing risks in highly interconnected markets.